Infants' prenatal exposure to opioids and the association with birth outcomes: A systematic review and meta‐analysis. Issue 1 (10th November 2021) - Graeve, Richard; Balalian, Arin A.; Richter, Matthias; Kielstein, Heike; Fink, Astrid; Martins, Silvia S.; Philbin, Morgan M.; Factor‐Litvak, Pam
Abstract: Background: Prenatal exposure to opioids (PEO) is a worldwide public health issue. Opioids cross the placental barrier and may affect the developing foetus and the birth outcomes. Objectives: This review aimed to explore newborns' weight, length and head circumference, preterm birth, and perinatal death as primary outcomes in relation to PEO. The secondary outcomes were gestational age at birth, Apgar scores and length of hospitalisation after delivery. Data sources: PubMed, Embase, PsycInfo and the Web of Science. Study selection and data extraction: Inclusion criteria were (i) cohort, case‐control or cross‐sectional peer‐reviewed studies published in English through 1 March 2021; (ii) comparing outcomes between prenatal exposed and unexposed groups to opioids (prescribed or obtained illegally). Exclusion criteria were foetal alcohol syndrome and non‐opioid primary exposure. Synthesis: Data were extracted by two authors. The Newcastle‐Ottawa Quality Assessment Scale was used for study quality assessment. Due to heterogeneity across studies, we used random effects models to obtain pooled standardised mean difference (SMD), pooled risk ratio (RR) and 95% confidence interval (CI). Results: Data from 80 studies were extracted. In meta‐analyses, opioid‐exposed neonates had lower birthweight (SMD −0.77, 95% CI −0.90, −0.64, I 2 = 82%), smaller head circumference (SMD −0.67, 95% CI −0.86, −0.48, I 2 = 84%), shorter birth length (SMD −0.97, 95% CI −1.24, −0.70, I 2 = 91%) and gestational age (SMD −0.45, 95% CI −0.60, −0.30, I 2 = 80%) than unexposed neonates. Pooled risks of neonatal death and preterm birth were higher among opioid‐exposed compared to unexposed neonates (RR 4.05, 95% CI 2.12, 7.72, I 2 = 73%; and RR 1.92, 95% CI 1.57, 2.35, I 2 = 99%). Conclusions: We found increased risks of adverse birth outcomes in relation to PEO. Caution should be used in interpreting the findings, as many studies were rated as poor quality, and with substantial inter‐study heterogeneity. Future studies should ensure comparability of opioid‐exposed and ‐unexposed group to strengthen internal validity.